IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI MATA PELAJARAN KETAMANSISWAAN PADA SISWA SD TAMAN MUDA IBU PAWIYATAN TAMANSISWA YOGYAKARTA TAHUN AJARAN 2015/2016 - Etik Winarni (Universitas Sarjanawiyata Tamansiswa, 2016)
Research to describe the implementation of character education through subjects Ketamansiswaan in elementary student’s Taman Muda Ibu Pawiyatan Tamansiswa Yogyakarta. The study, including research a qualitative. The subjects of this study consists of one headmaster, two teachers Ketamansiswaan, and six student at grade I to grade VI. The data collection this study uses interview, observation and documentation. The data collected were tested the validity of the way the extension of the participation, increased diligance, and triangulation. The data analysis for an interview with the collection of data, the reduction of data, the presentation of data, and the with drawal of the conclusion. The results of research showed that the implementation of character education through the Subject Ketamansiswaan in SD Taman Muda Ibu Pawiyatan Tamansiswa Yogyakarta academic year 2015/2016 is 1) the character education in lerningKetamansiswaan in the public has been implemented. The execution of the implementation of character education in primary school, Taman Muda Ibu Pawiyatan Tamansiswa Yogyakarta is habituation, integration into subjects, there are particular Ketamansiswaan, into the extra, there is also when boarding flash unit. In learning Ketamansiswaan own children are through the song or dolanan the child, 2) values of characters that appear each child is not the same or different with each other, values that includes the value of obedience, decency, neatness, culture and education. As for the characterto come out but has not yet appeared in learning Ketamansiswaan usually occurs in students a hyperactive on super active. In addition depends on the atmosphere or mood, 3) the obstacles that have emerged that many ABK. In fact, ABK can block and it’s hadr to be invited to work together well. The solution to overcome the barriers which are the handle students with special needs teacher should be extra patient. In addition, disseminate the program school to parents with how to use fliers, broadcast to television or radio, or the ceremony we announced to students or parents if any.